IoT Development Board for Engineering Applications - Aishwarya; Sneha, M.; Joshi, Vismaya; Kumar, J. Satheesh (IRO Journal on Sustainable Wireless Systems, 2022)
Technology developments in engineering applications has made life easier. Nowadays, Internet based computations and control are more popular. Internet of Things (IoT) is the latest improvements in industrial domain. This technology revolution satisfies the industrial requirements and societal needs. In the present scenario, most of society related research are carried out in the IoT domain. In this project, how the different sensors are being connected to the microcontroller and how the real-time data is collected and used as required by the application, have been discussed. It shows the advantages of the graphical view of the data output by which, the changes can be understood easily and in a more convenient way. This paper briefs about the IoT development board and the peripheral components. The methodology for interfacing the sensor and the communication with the cloud has also been detailed.
Keywords: Design board; sensor interfacing; wireless communication; IoT interfacing; cloud communication